2020
DOI: 10.15252/embr.201948927
|View full text |Cite
|
Sign up to set email alerts
|

ER stress in antigen‐presenting cells promotes NKT cell activation through endogenous neutral lipids

Abstract: CD1d‐restricted invariant natural killer T (iNKT) cells constitute a common glycolipid‐reactive innate‐like T‐cell subset with a broad impact on innate and adaptive immunity. While several microbial glycolipids are known to activate iNKT cells, the cellular mechanisms leading to endogenous CD1d‐dependent glycolipid responses remain largely unclear. Here, we show that endoplasmic reticulum (ER) stress in APCs is a potent inducer of CD1d‐dependent iNKT cell autoreactivity. This pathway relies on the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 76 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…Furthermore, the CD1-restricted TCRs of NKT cells are autoreactive to CD1 expressing APCs ( Cardell et al., 1995 ; Skold et al., 2003 ; Almeida et al., 2019 ). Indeed, endoplasmic reticulum (ER) stress in APCs is a potent inducer of CD1d-dependent NKT cell auto-reactivity ( Govindarajan et al., 2020 ).…”
Section: Nkt Cell Antigensmentioning
confidence: 99%
“…Furthermore, the CD1-restricted TCRs of NKT cells are autoreactive to CD1 expressing APCs ( Cardell et al., 1995 ; Skold et al., 2003 ; Almeida et al., 2019 ). Indeed, endoplasmic reticulum (ER) stress in APCs is a potent inducer of CD1d-dependent NKT cell auto-reactivity ( Govindarajan et al., 2020 ).…”
Section: Nkt Cell Antigensmentioning
confidence: 99%
“…Additionally, ER stress decreased the expression of CD1d in hepatocytes, contributing to NKT cell dysregulation in fatty livers (140). However, ER stress in macrophages potently induced CD1d-dependent iNKT cell autoreactivity via IRE1α/PERK pathways, since macrophages undergoing ER stress generated the neutral lipids that were enriched and loaded onto CD1d to activate iNKT cells (141). HFD-enhanced ER stress in adipocytes suppressed Th2 cytokine expression, which modulated adipose tissue macrophage polarization toward M1 and mediated systemic insulin resistance (142).…”
Section: Lipotoxicitymentioning
confidence: 99%
“…In contrast to the pro-inflammatory effect of PA in macrophages, a recent study found that PA enhanced the degradation of RIDD on T-bet and gata-3 mRNA by inducing ER stress in iNKT cells, thereby suppressing the production of IL-4 and IFN-γ and attenuating arthritis ( Ko et al, 2017 ). In addition, ER stress induced IRE1α and PERK-dependent branches can increase lipid antigens bound to CD1d molecules, thereby enhancing iNKT cell activation ( Bedard et al, 2019 ; Govindarajan et al, 2020 ). This indicates that ER-stressed APCs can affect iNKT cell activation via CD1d.…”
Section: Endoplasmic Reticulum Quality Control and Immune Cellsmentioning
confidence: 99%